Readiness of Micro, Small and Medium Enterprises Using Information Technology (Study in Selayar District) - Andi Firmansyah; Nurhidayah A Yani; Grace T Pontoh; Arifuddin Arifuddin (AFEBI Accounting Review, 2021)
This istudy iexamines ithe ireadiness iof iMicro iSmall iand iMedium iEnterprises i(MSMEs) iin iSelayar iRegency iin iusing iInformation iTechnology i(IT). iThe ipopulation iin ithis istudy iis iall iemployees ior iemployees iwho iwork iin ithe iMSMEs isector iin iSelayar iIslands iRegency. iSampling iis using purposive sampling techniques. This research is a quantitative approach. The data in this study were collected using questionnaires, then analyzed descriptively with descriptive statistics and inferentially using multiple linear regression analysis with the help of the SPSS 20 program. The results showed that: (1) ipartially, ioptimism iand iinnovation ihave ia ipositive iand isignificant ieffect ion iMSMEs ireadiness iin iusing iInformation iTechnology, iwhile iinsecurity ihas ia inegative iand isignificant ieffect ion iMSMEs ireadiness iin iusing iInformation iTechnology iand idiscomfort idoes inot ihave ia isignificant iinfluence ion iMSMEs ireadiness iin iusing iInformation iTechnology iin iSelayar iRegency, iand i(2) isimultaneously, ioptimism, iinnovation, iinsecurity, iand idiscomfort ihave ia isignificant ieffect ion iMSMEs ireadiness iin iusing iInformation iTechnology iin iSelayar iRegency. Keywords: Information Technology, MSMEs, Selayar Islands Regency